Choreographies of Contagion: Mapping Virality and Performative Identity on TikTok - Anies Fatmawati; Henrietta Noir; Shasa Indriyani; Jujuk Maryati; Fakhrul Setiobudi (Enigma Institute, 2025)
The rise of TikTok has inaugurated a new paradigm of digital culture centered on embodied participation. This study investigates viral dance challenges, proposing a novel framework—